"It's Killing Us!" Narratives of Black Adults About Microaggression Experiences and Related Health Stress. (24th June 2015) - Hall, Joanne M.; Fields, Becky
Perceived racism contributes to persistent health stress leading to health disparities. African American/Black persons (BPs) believe subtle, rather than overt, interpersonal racism is increasing. Sue and colleagues describe interpersonal racism as racial microaggressions: "routine" marginalizing indignities by White persons (WPs) toward BPs that contribute to health stress. In this narrative, exploratory study, Black adults ( n = 10) were asked about specific racial microaggressions; they all experienced multiple types. Categorical and narrative analysis captured interpretations, strategies, and health stress attributions. Six iconic narratives contextualized health stress responses. Diverse mental and physical symptoms were attributed to racial microaggressions. Few strategies in response had positive outcomes. Future research includes development of coping strategies for BPs in these interactions, exploration of WPs awareness of their behaviors, and preventing racial microaggressions in health encounters that exacerbate health disparities.